2011
DOI: 10.1007/s11250-011-9934-x
|View full text |Cite
|
Sign up to set email alerts
|

Some productive characteristics and body measurements of Norduz goats of Turkey

Abstract: Productive characteristics and body measurements of Norduz goats, a native genetic resource in Turkey, were measured. The animals studied were brought from natural habitats to the farm of the Animal Science Department of Agricultural Faculty, Yüzüncü Yıl University. Least squares means of withers height (WH), body length (BL), chest width at back of withers (CWBW), chest depth (CD), chest girth (CG) and leg girth (LG) of Norduz does were 65.9 ± 1.08, 67.2 ± 1.08, 21.1 ± 0.88, 30.8 ± 0.62, 88.9 ± 1.78 and 60.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
5
3
Order By: Relevance
“…Table 5 shows the descriptive values for the body measurements of the Damascus and Kilis goats. The average WH of the Damascus and Kilis goats were higher than those reported by Aktepe (2009) in Kilis goats and by Bingöl et al (2011) in Norduz goats, but similar to those reported by Barıtçı and Adıgüzel (2017) in Damascus and by Ünalan and Ceyhan (2017) in Kilis goats. The average BL of the Damascus and Kilis goats (75.10 cm and 73.87 cm, respectively) were higher than those of Kilis goats (Aktepe, 2009, Alızadehasl and Ünal 2011, Ünalan and Ceyhan 2017, and similar to those of Damascus goats (Barıtçı and Adıgüzel 2017).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Table 5 shows the descriptive values for the body measurements of the Damascus and Kilis goats. The average WH of the Damascus and Kilis goats were higher than those reported by Aktepe (2009) in Kilis goats and by Bingöl et al (2011) in Norduz goats, but similar to those reported by Barıtçı and Adıgüzel (2017) in Damascus and by Ünalan and Ceyhan (2017) in Kilis goats. The average BL of the Damascus and Kilis goats (75.10 cm and 73.87 cm, respectively) were higher than those of Kilis goats (Aktepe, 2009, Alızadehasl and Ünal 2011, Ünalan and Ceyhan 2017, and similar to those of Damascus goats (Barıtçı and Adıgüzel 2017).…”
Section: Discussionsupporting
confidence: 83%
“…The average BL of the Damascus and Kilis goats (75.10 cm and 73.87 cm, respectively) were higher than those of Kilis goats (Aktepe, 2009, Alızadehasl and Ünal 2011, Ünalan and Ceyhan 2017, and similar to those of Damascus goats (Barıtçı and Adıgüzel 2017). The average CD of the Damascus and Kilis goats (33.06 cm and 32.58 cm, respectively) were higher than those reported by Aktepe (2009), Alızadehasl and Ünal (2011), and Ünalan and Ceyhan (2017) in Kilis goats, by Bingöl et al (2011) in Norduz goats, and by Karakuş (2016) in Hair goats and Saanen goats. The average CW of the Damascus and Kilis goats (20.50 cm and 20.40 cm, respectively) were higher than those reported by Karakuş (2016) in Hair goats and Saanen goats and by Barıtçı and Adıgüzel (2017) in Damascus goats, but similar to those reported by Bingöl et al (2011) and Ünalan and Ceyhan (2017) in Kilis goats.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Traditionally, animals are visually assessed, which is a subjective method of judgement (Abanikannda et al, 2002;Yakubu, 2003). In goats body growth and development, objective means (linear body measurements) for describing and evaluating body size and conformation characteristics (Bingol et al, 2011) would overcome many of the problems associated with visual evaluation (Shrestha et al, 1984). Body weight is the measurement used mostly to evaluate body development and carcass characteristics in animals (De Brito Ferreira et al, 2000;Kuzelov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the parameters of body size consist of four type indicators: body length, body width, body height and circumference (Mayaka et al 1996;Chen et al 2008;Shi et al 2008;Chacón et al 2011;Wang et al 2011;Bingöl et al 2012). In order to achieve sufficient accurate measurements, multiple views from different angles must be used.…”
Section: Camera Number and Layoutmentioning
confidence: 99%